2003
DOI: 10.1093/jn/133.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Increased Dietary Protein Modifies Glucose and Insulin Homeostasis in Adult Women during Weight Loss

Abstract: Amino acids interact with glucose metabolism both as carbon substrates and by recycling glucose carbon via alanine and glutamine; however, the effect of protein intake on glucose homeostasis during weight loss remains unknown. This study tests the hypothesis that a moderate increase in dietary protein with a corresponding reduction of carbohydrates (CHO) stabilizes fasting and postprandial blood glucose and insulin during weight loss. Adult women (n = 24; >15% above ideal body weight) were assigned to either a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
121
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(139 citation statements)
references
References 30 publications
8
121
1
9
Order By: Relevance
“…This study also showed higher concentration of hepatic protein and RNA in the gastrocnemius muscle of the supplemented group. These results indicated that leucine supplementation in rats submitted to food restriction stimulated body fat loss, improved hepatic protein status and protein synthesis ability in muscle.The authors did not consider the findings related to body composition striking, considering that some human studies have already evidenced that an increase in BCAA consumption can improve the body loss process (Layman et al, 2003a., Mourier et al, 1997Layman, 2003;Layman et al, 2003b). Furthermore, studies comparing diets with different protein concentrations demonstrated significant changes in body composition in groups on a high-protein diet, especially by reducing fat mass and lowering loss of lean body mass.…”
mentioning
confidence: 99%
“…This study also showed higher concentration of hepatic protein and RNA in the gastrocnemius muscle of the supplemented group. These results indicated that leucine supplementation in rats submitted to food restriction stimulated body fat loss, improved hepatic protein status and protein synthesis ability in muscle.The authors did not consider the findings related to body composition striking, considering that some human studies have already evidenced that an increase in BCAA consumption can improve the body loss process (Layman et al, 2003a., Mourier et al, 1997Layman, 2003;Layman et al, 2003b). Furthermore, studies comparing diets with different protein concentrations demonstrated significant changes in body composition in groups on a high-protein diet, especially by reducing fat mass and lowering loss of lean body mass.…”
mentioning
confidence: 99%
“…Better outcomes with HP diets compared with HC diets in ad libitum setting may be related to the greater acute satiety associated with protein compared with glucose or fat [79][80][81]. HP diets have also been shown to produce lower fasting and postprandial insulin levels [50,[82][83][84][85].…”
Section: Moderate Carbohydrate High-protein Low-fat Diets (~40% Carmentioning
confidence: 99%
“…While most studies found that HP and HC diets had no differential effects on total and LDL cholesterol levels, some have shown that either HP or HC diets produced better outcomes [67,73,74,86,87]. HP diets were also found to result in higher fasting glucose levels compared with HC diets during weight loss [82][83][84]87]. Replacing carbohydrate with protein resulted in an inconsistent effect on postprandial glucose.…”
Section: Moderate Carbohydrate High-protein Low-fat Diets (~40% Carmentioning
confidence: 99%
See 1 more Smart Citation
“…During the last decade the notion that athletes as well generally active population require greater protein intake than the currently RDA recommendation of 0.8 g/kg of body weight per day in healthy adults has become well accepted [1,2]. In addition, high protein diets have also become quite popular in general population as part of many weight reduction programs [3,4]. Differences in protein requirements for different types of athletes (i.e., endurance, strength/power) and non-athletes are well documented [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%